Copy Denture: The General Overview Among Dentists And Dental Technologists In Malaysia - Norlela Yacob; Nusima Mohamed; Tine Martine Winarti; Aida Ali; Safura Anita Baharin; Faizah Abdul Fatah; Wan Nor Syariza Wan Ali (Ectodermal Dysplasia Group Turkey, 2024)
Indexed by Scopus